2008
DOI: 10.1128/jvi.02440-07
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Depletion of CD11c + Dendritic Cells Delays Lymphoinvasion after Intraperitonal Scrapie Infection

Abstract: The involvement of immune cells in prion capture and transport to lymphoid tissues still remains unclear. To investigate the role of dendritic cells (DC), we used DTR ؉/؉ mice, a transgenic model designed to trigger short-term ablation of DC. Transient depletion of DC around the time of intraperitoneal infection delayed prion replication in the spleen, as followed by PrPsc amount, a specific hallmark of prion diseases. Consequently, neuroinvasion and incubation time of prion disease were delayed. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Moreover, DCs seem to disseminate PrP Sc to peripheral sites of neuroinvasion such as mesenteric lymphoid tissues (Huang and MacPherson 2004) and the spleen (Blattler et al 1997). Recent studies have demonstrated that the temporary depletion of dendritic cell impaired neuroinvasion following oral inoculation (Raymond et al 2007) and intraperitoneal infection (Cordier-Dirikoc and Chabry 2008). An up-todate in vitro study has shown that infected dendritic cells are able to transmit prions to primary neurons from the CNS by the intermediary of tunneling nanotubes (TNT) (Gousset et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DCs seem to disseminate PrP Sc to peripheral sites of neuroinvasion such as mesenteric lymphoid tissues (Huang and MacPherson 2004) and the spleen (Blattler et al 1997). Recent studies have demonstrated that the temporary depletion of dendritic cell impaired neuroinvasion following oral inoculation (Raymond et al 2007) and intraperitoneal infection (Cordier-Dirikoc and Chabry 2008). An up-todate in vitro study has shown that infected dendritic cells are able to transmit prions to primary neurons from the CNS by the intermediary of tunneling nanotubes (TNT) (Gousset et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To definitively demonstrate a central role for cDC in our model of arthritis, we used CD11cDTR transgenic mice, which have been used to reveal the importance of these cells in a variety of experimental systems (22,(30)(31)(32)(33). It is reported that depletion is not entirely specific to cDCs, impacting on low expressers of CD11c (34).…”
Section: Transient Depletion Of Cd11c + Cells Reduced Articular Pathomentioning
confidence: 99%
“…Following oral prion infection altered homeostasis in DC levels has been reported in intestinal Peyer’s patches [84]. Transient depletion of CD11c-expressing cells (a commonly used marker indicative of classical DC) revealed the ability to completely block or severely impair pathogenesis via oral and intraperitoneal routes [85,86]. This depletion strategy was observed to eliminate all MNP types from the intestine, including classical DC and macrophages, suggesting that neither transport nor degradation are actively occurring during depletion [87].…”
Section: Resultsmentioning
confidence: 99%